The livestock situation in Ethiopia - Montgolfier-Kouevi, C. de (International Livestock Centre for Africa, 1976)
Reviews the overall livestock situation in Ethiopia. Assesses ecological and institutional aspects such as, population, land tenure, political and administrative environments. Discusses livestock and meat production systems, processing and marketing of livestock products and the institutional framework of the research and prospects of on going development strategies.